Validation of NRG oncology/RTOG‐0129 risk groups for HPV‐positive and HPV‐negative oropharyngeal squamous cell cancer: Implications for risk‐based therapeutic intensity trials. Issue 12 (26th March 2019) - Fakhry, Carole; Zhang, Qiang; Gillison, Maura L.; Nguyen‐Tân, Phuc Felix; Rosenthal, David I.; Weber, Randal S.; Lambert, Louise; Trotti, Andy M.; Barrett, William L.; Thorstad, Wade L.; Yom, Sue S.; Wong, Stuart J.; et al.
Abstract : Background: Radiation Therapy Oncology Group (RTOG)‐0129 recursive partitioning analysis was the basis for risk‐based therapeutic intensification trials for oropharyngeal cancer (OPC). To the authors' knowledge, the question of whether RTOG‐0129 overall survival (OS) estimates for low‐risk, intermediate‐risk, and high‐risk groups are similar in other data sets or applicable to progression‐free survival (PFS) is unknown. Therefore, the authors evaluated whether survival differences between RTOG‐0129 risk groups persist at 5 years, are reproducible in an independent clinical trial, and are applicable to PFS, and whether toxicities differ across risk groups. Methods: Prospective randomized clinical trials were analyzed retrospectively. RTOG‐0129 evaluated standard versus accelerated fractionation radiotherapy concurrent with cisplatin. RTOG‐0522 compared the combination of cisplatin and accelerated fractionation with or without cetuximab. Patients with OPC with available p16 status and tobacco history were eligible. Results: There was a total of 260 patients and 287 patients, respectively, from RTOG‐0129 and RTOG‐0522, with median follow‐ups for surviving patients of 7.9 years (range, 1.7‐9.9 years) and 4.7 years (range, 0.1‐7.0 years), respectively. Previous OS differences in RTOG‐0129 persisted at 5 years. In RTOG‐0522, the 5‐year OS rates for the low‐risk, intermediate‐risk, and high‐risk groups were 88.1%, 69.9%, and 45.1%, respectively ( P for trend, <.001). The 5‐year PFS rates for the same 3 groups were 72.9%, 56.1%, and 42.2%, respectively. In RTOG‐0522 among a subgroup of patients considered to be at very good risk (p16‐positive disease, smoking history of ≤10 pack‐years, and classified with T1‐T2 disease with ipsilateral lymph nodes measuring ≤6 cm or T3 disease without contralateral or >6 cm lymph nodes), the 5‐year OS and PFS rates were 93.8% and 82.2%, respectively. Overall rates of acute and late toxicities were similar by risk group. Conclusions: RTOG‐0129 risk groups persisted at 5 years and were reproducible in RTOG‐0522. However, there was variability in the estimates. These data underscore the importance of long‐term follow‐up and appropriate patient selection in therapeutic deintensification trials. Abstract : To the authors' knowledge, the issue of whether Radiation Therapy Oncology Group (RTOG)‐0129 overall survival estimates for low‐risk, intermediate‐risk, and high‐risk groups are similar in other data sets or applicable to progression‐free survival is unknown. In the current study, RTOG‐0129 risk groups appear to persist at 5 years, are reproducible in RTOG‐0522, and can be applied to progression‐free survival. However, there is variability in the estimates, which underscores the importance of long‐term follow‐up in therapeutic deintensification.